Index of Financial Inclusion - Mandira Sarma (Indian Council for Research on International Economic Relations (ICRIER), 2008)
The promotion of an inclusive financial system is considered a policy priority in many countries. While the importance of financial inclusion is widely recognized, the literature lacks a comprehensive measure that can be used to measure the extent of financial inclusion across economies. This paper attempts to fill this gap by proposing an index of financial inclusion (IFI). The IFI is a multi-dimensional index that captures information on various dimensions of financial inclusion in one single digit lying between 0 and 1, where 0 denotes complete financial exclusion and 1 indicates complete financial inclusion in an economy. The proposed index is easy to compute and is comparable across countries.
Keywords: G00; G21; O16; 330; Financial inclusion; IFI; multi-dimensional index; normalized inverse Euclidean distance; Kapitalmarkttheorie; Finanzsektor; Soziale Ausgrenzung